Inferior vena cava diameter measurements from ultrasound in the normal and healthy term neonates within 1 week of life in Hospital USM - Sze Teik, Teoh (2015)
INTRODUCTION Inferior vena cava (IVC) measurement from ultrasound has been used widely in the medical care of adults, based on the clinician performed ultrasound (CPU) concept and numerous research have shown that it is reliable in predicting the intravascular volume accurately. In paediatric age groups, especially the neonatal population, there are only few research and limited reference at present. Hence, the normal reference values of the IVC diameter measurement within the neonates are questions to be answered. OBJECTIVE To produce and estimate the mean diameter of the hepatic IVC from ultrasound for the otherwise normal and healthy term newborn infants in HUSM and to compare the difference of these mean diameters, in between those neonates born within 48 hours of life and after 48 hours of life. METHODS A sample of 233 normal and otherwise healthy term neonates from the post natal ward and nursery were recruited over period of 6 months. Demographic data, haemodynamic parameters (heart rate and non invasive blood pressure) were collected, followed by portable ultrasound assessment by the author solely, while the neonates sleeping, measuring the IVC diameter in both the inspiratory and expiratory phase, from both the cross sectional and longitudinal views. RESULTS As overall (n=233), the mean of the maximal diameter of the IVC among the otherwise healthy and term neonates, in both the longitudinal and cross sectional views were reported as 2.64 mm (SD 0.79) and 2.58 mm (SD 0.74), respectively. The 95 % confidence intervals for the mean maximal IVC diameters were reported as 2.54 – 2.74 mm and 2.49 – 2.68 mm for both longitudinal and cross sectional views, respectively. Samples were divided into 2 subgroups, Group 1 (within 48 hours of life) (n=140) and Group 2 (after 48 hours of life) (n=93) for further analysis. The mean IVC diameters measured in between these 2 groups showed no statistical significant difference, in both the ultrasound views and all the measured diameters, as reflected by p-value from 0.6-0.95. CONCLUSION This study had produced and estimated the mean diameter of IVC, in both longitudinal and cross sectional views for healthy term neonates in HUSM, as illustrated in the results above. Both the mean diameters of the IVC, regardless of the ultrasound views, between Group 1 and Group 2 were comparable to each other with no statistical significance difference.